Archaeology on the Apulian - Lucanian Border - Small, Alastair (Archaeopress Publishing, 2022)
The broad valley of the Bradano river and its tributary the Basentello separates the Apennine mountains in Lucania from the limestone plateau of the Murge in Apulia in South East Italy. For millennia the valley has functioned both as a cultural and political divide between the two regions, and as a channel for new ideas transmitted from South to North or vice versa depending on the political and economic conditions of the time. Archaeology on the Apulian - Lucanian Border aims to explain how the pattern of settlement and land use changed in the valley over the whole period from Neolithic to Late Medieval, taking account of changing environmental conditions, and setting the changes in a broader political, social and cultural context. There are three levels of focus. The first is on the results of a field survey (1996-2006) in the Basentello valley by teams from the Universities of Alberta, Edinburgh, and Bari, directed by the authors. The second concerns the discoveries of earlier field surveys in the late 1960s and early 1970s undertaken in connection with excavations on Botromagno near Gravina in Puglia. The third is a much broader synthesis of the results of recent scholarship using archaeological, epigraphic and literary sources to reconstruct an archaeological history of the valley and the surrounding area. The creation of a vast imperial estate at Vagnari around the end of the 1st century BC and its long-lasting impact on the pattern of settlement in the area is a significant theme in the later chapters of the book.